La experiencia del retorno de los migrantes bolivianos desde España: la toma de la decisión y la reinserción en origen desde una perspectiva de género - Raquel Martínez Buján (Les Cahiers ALHIM)
The analysis of return decision-making processes and experiences of reintegration within migration scholarship has benefitted from incorporating a gender perspective. Using a qualitative methodology conducted in the cities of Cochabamba and La Paz (Bolivia), this article focuses on the gendering of the patterns and factors that underpin the motivations to return. The findings suggest that the patriarchal structure that positions men and women differently in both the labour market and family structures, explains the different migratory trajectories of returnees. With regards to the reintegration in the labour market in Bolivia, I argue that its success depends on the individual capacity to mobilise human and financial resources, a process that is associated to the type of return initiated.